Preliminary attempt at biological control of coconut leaf eating caterpillar, Opisina arenosella Walker using two Trichogramma species - S. K. Jalali; T. Venkatesan; K. S. Murthy; T. V. Bhaskaran; Y. Lalitha (International Coconut Community Journal, 2005)
A preliminary attempt was made for biological control of coconut leaf eating caterpillar, Opisina arenosella Walker, by releasing two Trichogramma species viz. T. chilonis Ishii and T. embryophagum Hartig @ 1,000 to 4,000 parasitised eggs per palm in Bangalore, India. The mean percent reduction in larval population by 75.6, 60.0, 33.3 and 50.0% in T. chilonis and 88.8%, 175.0, 66.7 and 75.0% in T. embryophagum was recorded in treated palms during 1st, 2nd, 3rd and 4th generation of the pest compared to untreated control. There was non- significant difference between various release rates irrespective of the species, indicating that lower release rate of 1,000 parasitised eggs/palm as adequate. On sentinel egg cards, parasitism was low 2.0 - 5.0%, 0.0 - 2.0% and 0.0% in T. chilonis, and T. embryophagum released palms and untreated control palms, respectively. The field trial gave an indication that Trichogramma could be a potential parasitoid against O. arenosella and it is suggested that the parasitoids could be released and tested on a large scale in endemic areas to authenticate efficacy.